An overview of effectiveness plant-based shortening in substituting lard properties towards bakery products / Nurul Nadhirah Said and Nur Rabiatul Adawiah Mohammad Noor - Said, Nurul Nadhirah; Mohammad Noor, Nur Rabiatul Adawiah (2021)
Animal-based fat like lard is a fatty substance known for imparting a flavourful, yeasty aroma and the perfect soft texture towards bakery products like cakes, pastries, and bread. The prohibition under religious restriction in using lard and high saturated fat content drove the usage of modified vegetable oils in the bakery industry. However, legislative limitations and health considerations of the trans-fat produced from modified vegetable oil causes abundant research on reduction of trans fat content in modified vegetable oils are conducted. Hence, this review aims to distinguish modification processes of vegetable-based fats and oils besides to study the simplest and economical vegetable-based fats and oils blends in replacing physicochemical and mechanical properties of lard and its effectiveness on bakery products. Several findings reported that the vegetable-based fat and oil blends displayed both β' and β- form polymorphs comparable to the polymorphic behaviour of lard. In addition, previous studies found similar consistency of vegetable-based fat and oil blends to lard in the range of 319.20 to 326.26 g/cm2 that yields a satisfactory plastic and spreadable. Subsequently, the vegetable-based fats and oil blends in substituting lard properties have been successfully proven by uniform thickness and width cookies produced by the lard and the blends. Despite the emerging trends of the modified vegetable fats and oil blends used in bakery products that possess a better reduction of trans-fat and saturated fat, conducting further investigation on the limitation of using them commercially in the food industry should be considered since these involve potential public health impact.